2007
DOI: 10.1016/j.polymdegradstab.2007.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Ferrocene and ferrocenium modified clays and their styrene and EVA composites

Abstract: Abstract:In this work, ferrocene-and ferrocenium-containing salts were employed to modify montmorillonite. X-ray measurements show an increase in the interlayer spacing upon clay modification, which means that the larger and more organophilic cations were inserted into the gallery space of montmorillonite. Attempts to prepare nanocomposites of polystyrene and ethylene vinyl acetate copolymers lead to immiscible systems; the morphology of these systems was elucidated with TEM, XRD and cone calorimetry. The ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…The cone calorimetry results obtained at 3% loading of the borate LDHs are consistent to those reported in previous work [33] , in which an LDH modified with 2-aminotoluene-5-sulfonate was melt blended with EVA at 3% loading and 39% reduction in PHRR was observed. They are also comparable to those observed for EVA composites containing MMT modified with a ferrocenium cation [34] . Ref.…”
Section: Flammability Behavior Of the Ethylene Vinyl Acetate Compositessupporting
confidence: 85%
“…The cone calorimetry results obtained at 3% loading of the borate LDHs are consistent to those reported in previous work [33] , in which an LDH modified with 2-aminotoluene-5-sulfonate was melt blended with EVA at 3% loading and 39% reduction in PHRR was observed. They are also comparable to those observed for EVA composites containing MMT modified with a ferrocenium cation [34] . Ref.…”
Section: Flammability Behavior Of the Ethylene Vinyl Acetate Compositessupporting
confidence: 85%
“…[13] Chen et al also used CTAB-modified clay and observed 11 C increase in T 10 by the addition of 5 wt.% clay. [14] Manzi-Nshuti et al in their studies on ferric-and ferrocenium-modified clay nanocomposites, observed that addition of 3 wt.% of 1,10-bis (n-hexadecyl) ferrocene-modified clay improved T 10 from 346 C to 418 C. [15] In the present system, the T 10 showed drastic changes especially in the low loadings as shown in Table 2. The T 10 for neat polystyrene is around 365 C and on addition of asphaltene, it increases to 440 C for St3 loading.…”
Section: Thermogravimetric Analysismentioning
confidence: 49%
“…In early work, the catalytic effect of metal centers on polyolefins has been studied in‐depth . The mechanism was described as that they can act as catalysts to enhance the reactivity of carbon deposition.…”
Section: Resultsmentioning
confidence: 99%